Ethical Considerations on Clinical Trials of Invasive Brain-computer Interface Technology - Sharina JIN; Xiaomei ZHAI (Yixue yu zhexue)
Invasive brain-computer interface (BCI) technology holds immense clinical application value, especially in neurological and psychiatric disorders. However, clinical trials involving this technology present unique ethical challenges that differ from traditional trials, in terms of both scope and priorities, despite superficial similarities to other emerging biotechnologies. Majority of research participants are patients with conditions for which there are no available treatments or who are at an advanced stage of the disease. And the purpose of the trial is both to gain knowledge and to address their health concerns. The trials not only need to follow the principle of risk minimization, but also need to be proportional to the severity of the disease. Invasive experiments on the human brain may affect the autonomy of the individual, therefore trials need to adapt the way of informed consent which called dynamic informed consent. In addition, the trial exposes more privacy leakage potential. Based on the above, researchers need to maintain heightened attention to the ethical considerations of invasive BCI clinical trials.